Pengaruh Kompetensi, Independensi dan Pengalaman Kerja Auditor terhadap Kualitas Audit dengan Etika Auditor Sebagai Variabel Moderasi (Studi Empiris Kantor Akuntan Publik di Semarang, Solo dan Yogyakarta) - Risky Fitri Septiana; Jaeni Jaeni (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
The purpose of this study is to analyze auditor ethics as a moderating variable affecting competence, independence and work experience on audit quality at public accounting firms in Semarang, Solo and Yogyakarta. The variables used are competence, independence and work experience as independent variables while the dependent variable is audit quality and auditor ethics as moderating variables. In this study using a questionnaire in data collection as many as 16 Public Accounting Firms with a number of 101 respondents used as samples. The data analysis technique used a measurement scale technique, data feasibility test, classical assumption test, multiple linear regression analysis, moderated regression analysis, and the coefficient of determination (R2). The results of this study reveal that competence has a significant effect on audit quality, while independence and work experience have no effect on audit quality. Auditor ethics cannot moderate the effect of competence, independence and work experience on audit quality.